Developmental Evaluation - Evaluation, Better
Developmental Evaluation (DE) is an evaluation approach that can assis t social innovators develop social change initiatives in complex or un certain environments. DE originators liken their approach to the role of research & development in the private sector product development pr ocess because it facilitates real-time, or close to real-time, feedbac k to program staff thus facilitating a continuous development loop. Mi chael Quinn Patton is careful to describe this approach as one choice that is responsive to context. This approach is not intended as the so lution to every situation. Development evaluation is particularly suit ed to innovation, radical program re-design, replication, complex issu es, crises In these situations, DE can help by: framing concepts, test quick iterations, tracking developments, surfacing issues. This descr iption is from Patton (2010) Developmental Evaluation. Applying Comple xity Concepts to Enhance Innovation and Use... "Developmental Evaluati on supports innovation development to guide adaptation to emergent and dynamic realities in complex environments. Innovations can take the f orm of new projects, programs, products, organizational changes, polic y reforms, and system interventions. A complex system is characterized by a large number of interacting and interdependent elements in which there is no central control. Patterns of change emerge from rapid, re al time interactions that generate learning, evolution, and developmen t – if one is paying attention and knows how to observe and capture th e important and emergent patterns. Complex environments for social int erventions and innovations are those in which what to do to solve prob lems is uncertain and key stakeholders are in conflict about how to pr oceed."